KINERJA OPERASIONAL PELABUHAN PERIKANAN DI PERAIRAN TELUK SEMANGKA KABUPATEN TANGGAMUS LAMPUNG - Khoerul Fatoni; Iin Solihin; Retno Muninggar (Bogor Agricultural University, 2021)
The Semangka Bay in Tanggamus Regency of Lampung Province is a potential area for capture fisheries activities. The fishing port as the primary basis for the capture fisheries sector can increase regional economic growth. The fishing ports in Tanggamus Regency have physical and non-physical problems, so efforts to develop fishing ports are needed. The preparation of these efforts required information about the operational conditions of fishing ports. This study aims to describe the operational conditions of the fishing port in the Tanggamus Regency. The research method is descriptive with two stages. The first assessment of the operational performance of fishing ports. Second, gap assessment of fishing ports. The result showed that the average value of fishing ports operational performance is 26%, and the average gap value is 74%. The operational condition of the fishing ports in the Tanggamus Regency is classified as inferior. Fishing port facilities are the criteria with the lowest performance and the highest gap. Improvements to the fishing ports in Tanggamus Regency are needed through procurement and repair of fishing port facilities by local governments.